READING BEYOND THE STROKES: A SEMIOTIC ANALYSIS OF EDITORIAL CARTOONS ON A CAMPUS NEWSPAPER OF A HIGHER EDUCATION INSTITUTION IN THE PHILIPPINES - Benjamin Baguio Mangila (Universitas Islam Negeri Alauddin Makassar, 2021)
Editorial cartoons have an unchallenged history as a unique and important artefact in both political and cultural discourses. In journalism, they offer varied insights and may eventually alter beliefs and opinions, influence politics, trigger discussions, and give life to ideas. This paper investigates the signs and meanings of editorial cartoons published in a campus newspaper of a tertiary school in the Philippines. It anchors on Chandler’s semiotic concepts in analyzing the editorial cartoons that incorporate both the Saussurean dyadic concept of signs, signifier and signified, and the Peircean triadic concept of signs as symbolic indexical, and iconic. It also considers Leymore’s idea of the figure and ground, which identifies the primary, secondary, and tertiary signifiers based on their importance or impact on editorial cartoons. Analysis shows that editorial cartoons contain all types of signifiers, primary, secondary, and tertiary, which work together to effectively convey the intended meanings to its target readers. These signifiers also possess certain characteristics as being symbolic, indexical, and iconic and they blend together to enrich the editorial cartoons’ intended meanings. Furthermore, these editorial cartoons illustrate the newspaper’s perceptions as well as its stand on various issues and concerns relating or affecting the students and the whole academic community. Although these editorial cartoons are only published in the campus newspaper, they do not only deal with important local issues and concerns but in the national and global spheres as well.